Chinese vinegar classification via volatiles using long-optical-path infrared spectroscopy and chemometrics. (1st March 2016) - Dong, D.; Zheng, W.; Jiao, L.; Lang, Y.; Zhao, X.
Highlights: First study of Chinese vinegar classification via volatiles using FTIR. Spectral characteristics of the vapors from vinegars were observed. Spectral differences among the vapors from different brands of vinegars were studied. The ability of FTIR combined with chemometrics to discriminate vinegars was demonstrated. Abstract: Different brands of Chinese vinegar are similar in appearance, color and aroma, making their discrimination difficult. The compositions and concentrations of the volatiles released from different vinegars vary by raw material and brewing process and thus offer a means to discriminate vinegars. In this study, we enhanced the detection sensitivity of the infrared spectrometer by extending its optical path. We measured the infrared spectra of the volatiles from 5 brands of Chinese vinegar and observed the spectral characteristics corresponding to alcohols, esters, acids, furfural, etc. Different brands of Chinese vinegar had obviously different infrared spectra and could be classified through chemometrics analysis. Furthermore, we established classification models and demonstrated their effectiveness for classifying different brands of vinegar. This study demonstrates that long-optical-path infrared spectroscopy has the ability to discriminate Chinese vinegars with the advantages that it is fast and non-destructive and eliminates the need for sampling.